1961
DOI: 10.1149/1.2428229
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Silver Oxide Determined by Means of Neutron Diffraction

Abstract: The crystal structure of normalAgO has been determined by means of neutron diffraction. The nuclear scattering of Ag and O atoms has made it possible to determine the positions of the oxygen atoms and to modify the space group which was reported for this compound from x‐ray data. No magnetic diffractions were observed even at liquid helium temperature; the absence of magnetic scattering confirms the diamagnetism of the compound. The lattice was found to be monoclinic, space group P21/normalc , with four for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

1965
1965
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 0 publications
4
53
0
Order By: Relevance
“…It has been suggested that Ag lin can be attributed to Ag with an oxidation state of +1 ͑Ag I ͒ and that Ag sq can be attributed to Ag with an oxidation state of +3 ͑Ag III ͒. 8 AgO has been reported to be diamagnetic, 9 which is consistent with spin paired configurations of linearly coordinated 4d 10 Ag I , and square planar 4d 8 Ag III . 13 The coordination environments around the Ag ions in AgO are also consistent with the coordination environments of Ag I in Ag 2 O ͑Ref.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been suggested that Ag lin can be attributed to Ag with an oxidation state of +1 ͑Ag I ͒ and that Ag sq can be attributed to Ag with an oxidation state of +3 ͑Ag III ͒. 8 AgO has been reported to be diamagnetic, 9 which is consistent with spin paired configurations of linearly coordinated 4d 10 Ag I , and square planar 4d 8 Ag III . 13 The coordination environments around the Ag ions in AgO are also consistent with the coordination environments of Ag I in Ag 2 O ͑Ref.…”
Section: Introductionmentioning
confidence: 96%
“…6 Although not as widely studied as Ag 2 O, several structural and spectroscopic studies have been carried out on AgO in an effort to elucidate the geometry and electronic structure of the material. [7][8][9][10][11][12] AgO crystallizes in a monoclinic structure ͑space group P12 1 / c1͒ with Ag ions in two distinct coordination environments. 7 Neutron-diffraction experiments have indicated that it is composed of linearly coordinated Ag ions ͑denoted Ag lin ͒ and Ag ions in a slightly distorted square planar coordination with four oxygens 8 ͑denoted Ag sq ͒, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…If these inferences are correct, it would follo~v that the true crystalline phase AgzO3 is liliely face-centered cubic, lilie Ag,O, and not inonoclinic lilie Ago (9). Indeed the structures of the nitrate-and sulfate-stabilized higher oxides, Agin'Oll and Ag,SOl,, and often confused with Ag203, are close to that of Ag2O (7,8).…”
Section: Cozllombic Il~eusz~rementsmentioning
confidence: 99%
“…The resulting compounds were characterized by X-Ray diffraction confirming the presence of cubic Ag 2 O in the first oxidation step and a mixture of Ag 2 O and AgO in the last one (see figure 2). It should be noted that AgO is not a Ag(II) phase but has been shown to contain Ag(I) and Ag(III) by means of neutron diffraction [16] and EXAFS data [17][18] .…”
Section: Resultsmentioning
confidence: 99%